The importance of the presence of the dental surgeon in a hospital scope – literature review - Costa, Maria Clotilde Barbosa (2020)
Objective: This study aims to elucidate the respect for the importance of the presence of the dentist in the hospital, focusing on the benefits that comprehensive care generates for inpatients. Methodology: This is a literature review, with the following question as a guiding question: What are the benefits that the presence of the dentist brings in the hospital? For the research, the descriptors were defined and used: Oral Hygiene, Health Personnel and Hospital, found through the platform DeCS - Descriptors in Health Sciences and searched on the platforms: Latin American and Caribbean in Health Sciences (LILACS) and US National Library of Medicine (PubMed). The inclusion criteria were articles published in the last ten years, available in full and published in dental journals. The exclusion criteria were monographs and articles that did not answer the guiding question. Results: After applying the filters, 238 articles remained for reading abstracts. That done and after discarding the repeated articles, 116 articles were selected to be read in full. Of these, a total of 31 articles were used and served as the basis for the study. Conclusion: The implementation of a dental surgeon to the multidisciplinary team of a hospital provides greater security in the diagnosis of oral diseases, as it is an intimate professional in the area. In addition to providing assistance to nursing professionals, who are responsible for performing oral hygiene of the sick, making these procedures clearer and better performed.